P14-10 Genome-Wide DNA Methylation Profiles Associated with Diesel Exhaust Particulate Matter in Bladder Spheroids - H.R. Dhaini; W. Abou-Kheir; C. Afif; A. Ghantous; M. Fadel; J. Sciare; D. Courcot; F. Ledoux; A. Kurdi; A. Yehya; N. Fakhri; M. El Kawak (Toxicology Letters, 2025)

Comparison of submerged and air liquid interface exposure: limitations and differences in the toxicological effects evaluated in bronchial epithelial cells - Y. Allouche; S. Marchetti; R. Bengalli; G. Motta; L. Pagliarulo; F. Cazier; S. Achard; M. Fadel; P. Mantecca; D. Courcot; F. Ledoux; A. Verdin; et al. (Environmental Research, 2025)

Coastal hydrodynamics at the sub-Antarctic Possession Island (Crozet archipelago) inferred from bedform structures and sediment properties - Yann Lelièvre; Guillaume Lawnizack; Nadia K. Ayoub; Francesco d'Ovidio; Éric Armynot du Châtelet; Mario Zampolli; Georgios Haralabus; Lucie Courcot; Pierre-Yves Collin; Thomas Saucède (Marine Geology, 2025)

P21-42 Impact of Organic Extractable Matter (OEM) from PM2.5 collected in Lebanon on human bronchial epithelial cells: insights into autophagy, mitophagy, and cell senescence Activation - M. Chwaikani; A. Verdin; G. Badran; I. Abbas; N. Jaber; M. Roumie; D. Courcot; F. Ledoux; G. Garçon (Toxicology Letters, 2024)

P21-36 Effects of air pollution in asthmatic children: personal exposure to pollutants and biomarkers of effect in exhaled breath condensates - A. Verdin; M. Migan; F. Cazier; N. Verbrugghe; N. Jaber; A. Dega; A. Kakpo; L. Adonouhoue; F. Sagbo; D. Dewaele; F. Aissi; B. Cachon; et al. (Toxicology Letters, 2024)

Use of potentially toxic elements in sedimentable industrial dust to trace their input in soils (Northern France) - M. Casetta; L. Courcot; J. Caillaud; D. Dumoulin; V. Alaimo; V. Cornille; G. Billon; D. Courcot; M. Hermoso; S. Philippe (Journal of Soils and Sediments, 2024)

Ascorbate oxidation driven by PM2.5-bound metal(loid)s extracted in an acidic simulated lung fluid in relation to their bioaccessibility - A. Expósito; B. Markiv; M. Santibáñez; M. Fadel; F. Ledoux; D. Courcot; I. Fernández-Olmo (Air Quality, Atmosphere & Health, 2024)
The oxidative potential (OP) is defined as the ability of inhaled PM components to catalytically/non-catalytically generate reactive oxygen species (ROS) and deplete lung antioxidants. Although several studies have measured the OP of particulate matter (PM OP) soluble components using different antioxidants under neutral pH conditions, few studies have measured PM OP with acidic lung fluids. This study provides new insights into the use of acidic rather than neutral fluids in OP assays. Thus, the first aim of this study was to clarify the effect of using an acidic lung fluid on ascorbic acid (AA) depletion. This was achieved by measuring the oxidative potential (OP-AA) of individual compounds known to catalyze the AA oxidation (CuSO 4 , CuCl 2 , and 1,4-NQ) in artificial lysosomal fluid (ALF, pH 4.5), a commonly used acidic simulated lung fluid, and in a neutral fluid (phosphate-buffered saline (PBS1x), pH 7.4). Our results from these individual compounds showed a significant decrease of OP-AA in the acidic fluid (ALF) with respect to the neutral fluid (PBS). Then, the second aim of this work was to investigate whether the OP-AA assay could be applied to PM 2.5 samples extracted in acidic conditions. For this purpose, OP-AA and bioaccessible concentrations of metal(loid)s (V, Mn, Fe, Ni, Cu, Zn, As, Mo, Cd, Sb, and Pb) of PM 2.5 samples collected in an urban-industrial area that were extracted in ALF were analyzed. The mean volume-normalized OP (OP-AAv) value was 0.10 ± 0.07 nmol min −1 m −3 , clearly lower than the values found in the literature at neutral pH. OP-AAv values were highly correlated with the ALF-bioaccessible concentration of most of the studied metal(loid)s, mainly with Cu and Fe.